Apostasy on Christian Era - de Aguiar, Adenilton Tavares (Kerygma, 2018)
This paper deals with a brief analysis on the term last days and its correlates throughout the Bible with emphasis on the Pastoral Epistles. The paper is split into three parts. The first one deals with some Old Testament passages containing allusions to the messianic age or to the end of History. The second one explores the Christological meaning of the term last days and its correlates in the New Testament. Finally, the third one focuses on the Pastoral Epistles by assessing the phrases in later times (1 Tim 4:1), in the later days (2 Tim 3:1), and the time is coming (2 Tim 4:3). The analysis of the data will show that Paul and the other New Testament writers understood that they were already living on the last days, and that the apostasy which was already at work in their own time would increase until reach its climax on the time immediately before the second Coming of Christ.